2017
DOI: 10.1002/eap.1535
|View full text |Cite
|
Sign up to set email alerts
|

Species’ traits help predict small mammal responses to habitat homogenization by an invasive grass

Abstract: Invasive plants can negatively affect native species, however, the strength, direction, and shape of responses may vary depending on the type of habitat alteration and the natural history of native species. To prioritize conservation of vulnerable species, it is therefore critical to effectively predict species' responses to invasive plants, which may be facilitated by a framework based on species' traits. We studied the population and community responses of small mammals and changes in habitat heterogeneity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 112 publications
(161 reference statements)
2
20
1
Order By: Relevance
“…Our observation of a negative linear trend for abundance of cricetids in relation to cheatgrass cover is in agreement with the majority of investigations examining effects of cheatgrass on rodents at the individual species (Hall ) and community levels (Ostoja and Schupp , Freeman et al. , but see Ceradini and Chalfoun ). The species comprising the family Cricetidae in our study area represented several foraging guilds (e.g., granivores, folivores, and carnivores), but were similar in that they were all relatively small and reliant upon quadrupedal motion.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our observation of a negative linear trend for abundance of cricetids in relation to cheatgrass cover is in agreement with the majority of investigations examining effects of cheatgrass on rodents at the individual species (Hall ) and community levels (Ostoja and Schupp , Freeman et al. , but see Ceradini and Chalfoun ). The species comprising the family Cricetidae in our study area represented several foraging guilds (e.g., granivores, folivores, and carnivores), but were similar in that they were all relatively small and reliant upon quadrupedal motion.…”
Section: Discussionsupporting
confidence: 91%
“…This finding for Ord's kangaroo rats is not entirely unique for rodents. For example, Ceradini and Chalfoun () observed that deer mice abundance increased marginally with cheatgrass abundance. In addition, Pearson and Fletcher () and Malick et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the extent that novel weapons influence the feeding preferences of generalist vertebrates (e.g., Kalisz, Spigler, & Horvitz, 2014) in invaded communities is generally unclear. Alternatively, native rodents in the Great Basin could avoid cheatgrass seeds relative to seeds from native competitors due to inferior nutritional quality (Kelrick & MacMahon, 1985) and/or effective physical defenses (e.g., persistent awns) (Ceradini & Chalfoun, 2017).…”
Section: Discussionmentioning
confidence: 99%